2009
DOI: 10.1016/j.virol.2009.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Peruvian horse sickness virus and Yunnan orbivirus, isolated from vertebrates and mosquitoes in Peru and Australia

Abstract: During 1997, two new viruses were isolated from outbreaks of disease that occurred in horses, donkeys, cattle and sheep in Peru. Genome characterization showed that the virus isolated from horses (with neurological disorders, 78% fatality) belongs to a new species the Peruvian horse sickness virus (PHSV), within the genus Orbivirus, family Reoviridae. This represents the first isolation of PHSV, which was subsequently also isolated during 1999, from diseased horses in the Northern Territory of Australia (Elsey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 43 publications
6
65
0
Order By: Relevance
“…The VP1 of the two isolates showed >90% amino acid identity to the prototype YOUV strain isolated from Culex tritaeniorhynchus mosquitoes collected in Yunnan province of China (Attoui et al, 2005). Subsequent phylogenetic studies have shown that Yunnan orbivirus is a species complex that includes three closely related serotypes: Yunnan virus, isolated from mosquitoes in China and Indonesia; Rioja virus, isolated from cattle, sheep, donkeys and a dog in Peru; and Middle Point virus, isolated from a cow in Australia (Attoui et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…The VP1 of the two isolates showed >90% amino acid identity to the prototype YOUV strain isolated from Culex tritaeniorhynchus mosquitoes collected in Yunnan province of China (Attoui et al, 2005). Subsequent phylogenetic studies have shown that Yunnan orbivirus is a species complex that includes three closely related serotypes: Yunnan virus, isolated from mosquitoes in China and Indonesia; Rioja virus, isolated from cattle, sheep, donkeys and a dog in Peru; and Middle Point virus, isolated from a cow in Australia (Attoui et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Baculoviruses, which have only ever been isolated from arthropods, can transduce mammalian cells via direct fusion with the plasma membrane, but cannot replicate in these cells (Blagborough et al, 2010), suggesting that they could not productively infect mammalian species. Certain mosquito-borne arboviruses, such as Yunnan orbivirus (YUOV -genus Orbivirus, family Reoviridae) or Banna virus (BAV -genus Seadornavirus, family Reoviridae) have also been replicated successfully in BSR cells but not in other mammalian cells, such as Vero or BHK-21 (Attoui et al, 2009;Cowled et al, 2007). Both BAV and YUOV were isolated from both vertebrates (in which they cause disease) and mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…The 97-100% similarity for individual genes indicated that they both belong to PHSV serotype 1. 1 The epidemiology of the infections caused by PHSV and Elsey is poorly characterized.…”
Section: Brief Communicationmentioning
confidence: 99%
“…1 Although the possibility that ELSV causes neurologic syndromes in horses may be reasonably high, these viruses have also been isolated from healthy horses. Significant differences between Australian ELSV and PHSV from South America were noted.…”
Section: Brief Communicationmentioning
confidence: 99%